Navigating Sustainability: Bank Dynamics, Market Structure, and Enterprise Risk Management in ASEAN Exchanges - Jane Naomi; Dewi Hanggraeni (Eduvest - Journal of Universal Studies, 2025)
The banking sector plays a vital role in economic stability and sustainable development. As financial institutions face increasing pressure to align profitability with Environmental, Social, and Governance (ESG) commitments, Enterprise Risk Management (ERM) has gained prominence as a tool for enhancing both financial outcomes and ESG performance. While prior research has explored the impact of bank characteristics and industry concentration on performance, the mediating role of ERM remains underexamined, especially in emerging markets. This study addresses this gap by investigating how bank characteristics (ownership concentration, complexity, international diversification) and industry concentration affect financial and ESG performance, with ERM as a mediating variable. The analysis draws on data from ASEAN-listed banks between 2019 and 2023 using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that ownership concentration negatively influences financial performance, whereas bank complexity and international diversification have no significant financial effects. Industry concentration also lacks a significant financial impact. For ESG performance, bank complexity and international diversification show positive effects, while ownership concentration has no influence and industry concentration exerts a negative effect. ERM does not mediate relationships with financial performance or the effect of industry concentration on ESG outcomes. However, it mediates the relationship between international diversification and ESG performance. The findings highlight the conditional role of ERM in advancing ESG goals, especially in internationally diversified banks. Regulators are urged to revisit ownership concentration policies, and banks are encouraged to integrate ESG into core strategies and reinforce governance frameworks to manage structural risks.